Retroauricular/Transcranial Color-Coded Doppler Ultrasound Approach in Junction With Ipsilateral Neck Compression on Real-Time Hydroacoustic Variation of Venous Pulsatile Tinnitus - Gao, Xiuli; Hsieh, Yue-Lin; Wang, Xing; Wang, Wuqing (Frontiers in Human Neuroscience, 2022)
Alterations in dural venous sinus hemodynamics have recently been suggested as major contributing factors to venous pulsatile tinnitus (PT). Nevertheless, little is known about the association between real-time alterations in hemodynamics and the subjective perception of venous PT. This study aimed to investigate the hydroacoustic correlations among diverticular vortices, mainstream sinus flow, and PT using various Doppler ultrasound techniques. Nineteen venous PT patients with protrusive diverticulum were recruited. The mainstream sinus and diverticular hemodynamics before and after ipsilateral internal jugular vein (IJV) compression were investigated using an innovative retroauricular color-coded Doppler (RCCD) method to examine the correlation between the disappearance of PT and hemodynamic alterations. To reveal the hydroacoustic characteristics of disparate segments of venous return, a computational fluid dynamics (CFD) technique combined with the transcranial color-coded Doppler method was performed. When the ipsilateral IJV was compressed, PT disappeared, as the mean velocity of mainstream sinus flow and diverticular vortex decreased by 51.2% and 50.6%, respectively. The vortex inside the diverticulum persisted in 18 of 19 subjects. The CFD simulation showed that the flow amplitude generated inside the transverse-sigmoid sinus was segmental, and the largest flow amplitude difference was 20.5 dB. The difference in flow amplitude between the mainstream sinus flow and diverticular flow was less than 1 dB. In conclusion, the sensation of PT is closely associated with the flow of kinetic energy rather than the formation of a vortex, whereby the amplitude of PT is correlated to the magnitude of the flow velocity and pressure gradient. Additionally, the range of velocity reduction revealed by the RCCD method may serve as a presurgical individual baseline curative marker that may potentially optimize surgical outcomes.